1994
DOI: 10.1029/93tc02231
|View full text |Cite
|
Sign up to set email alerts
|

Extension versus compression during the Miocene tectonic evolution of the Betic chain. Late folding of normal fault systems

Abstract: The westernmost part of the Mediterranean Alpine Belt is represented by the Betic‐Rif orogenic belt, around the Gibraltar Arc, which in turn surrounds the Alboran Basin. In the Betic Chain, early and middle Miocene crustal thinning of the Alboran basement is well established, as extensional low‐angle normal faults and detachment faults, developed in both ductile and brittle conditions, thinned a previously thickened crust. In the Alboran Domain of the central Betics, two main extensional episodes are evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 23 publications
1
98
0
3
Order By: Relevance
“…They revealed large-scale extension associated with HT metamorphism (among others Fernandez et al, 2016;Negro et al, 2006;Platt and Whitehouse, 1999) and formation of crustal scale detachements (Augier et al, 2005;Caby et al, 2001;Crespo-Blanc et al, 1994;Jabaloy et al, 1993;Platt et al, 2005) producing deep unroofing during the Late OligoceneEarly Miocene, within the AlKaPeCa domain (Bruguier et al, 2009;Michard et al, 2006;Monié et al, 1992;Monié et al, 1994;Platt et al, 2003). This Miocene signal shows diachronous stages between the "AlKa" and "PeCa" domains, being older for the Peloritani and Calabria than for Alboran and the Kabylie basement (Michard et al, 2006;Platt et al, 2013 for the Betics-Rif-Tell data; Heymes et al, 2010;Rossetti et al, 2004Rossetti et al, , 2010 for the Peloritani-Calabria data).…”
Section: Extensional Deformation In Alkapeca Far Effects In the Forementioning
confidence: 99%
“…They revealed large-scale extension associated with HT metamorphism (among others Fernandez et al, 2016;Negro et al, 2006;Platt and Whitehouse, 1999) and formation of crustal scale detachements (Augier et al, 2005;Caby et al, 2001;Crespo-Blanc et al, 1994;Jabaloy et al, 1993;Platt et al, 2005) producing deep unroofing during the Late OligoceneEarly Miocene, within the AlKaPeCa domain (Bruguier et al, 2009;Michard et al, 2006;Monié et al, 1992;Monié et al, 1994;Platt et al, 2003). This Miocene signal shows diachronous stages between the "AlKa" and "PeCa" domains, being older for the Peloritani and Calabria than for Alboran and the Kabylie basement (Michard et al, 2006;Platt et al, 2013 for the Betics-Rif-Tell data; Heymes et al, 2010;Rossetti et al, 2004Rossetti et al, , 2010 for the Peloritani-Calabria data).…”
Section: Extensional Deformation In Alkapeca Far Effects In the Forementioning
confidence: 99%
“…Comas et al, 1992;García-Dueñas et al, 1992) provides key issues for the timing and tectonic context of the brittle faulting affecting the Alpujarride Complex. In particular, Crespo-Blanc et al (1994) and Crespo-Blanc (1995) showed that extension liked to the Contraviesa fault system was active during Burdigalian-Langhian times (approximately 20.5-15 Ma, according to Berggren et al (1985)). Moreover, the lower Burdigalian generalised marine transgression in the inner part of the Gibraltar Arc suggests that the onset of extension in that region took place possibly at the Oligocene-Miocene boundary (Rodríguez-Fernández et al, 1999).…”
Section: Age Of Exhumationmentioning
confidence: 99%
“…This faulting event is also responsible for the tectonic elision and thinning of the nappe sequences and can be thus referred to as the Early Miocene phases of the Alboran rifting. In particular, it can be tentatively ascribed to the Contraviesa extensional fault system of Crespo-Blanc et al (1994) for the style of deformation and the associated extension direction.…”
Section: Age Of Exhumationmentioning
confidence: 99%
See 2 more Smart Citations